Genetic Component And Character Association Studies For Grain Yield Wheat (Triticum Aestivum L.) (International Journal of Food and Nutritional Sciences, 2022)
Wheat (Triticum aestivum L.) is one the most important cereal crop grown worldwide. The genetic improvement of any breeding population largely depends on the extent of genetic variability present in a crop species. In the present investigation, forty diverse bread wheat genotypes were evaluated for genetic variability, heritability, and genetic advance at the Research Farm of Faculty of Agricultural Sciences and Allied Industries, Rama University, Kanpur-209217 during 2021-22. The genotypes were grown in RBD with 3 replications and data were collected on eleven morphological characters. Analysis of variance showed highly significant differences among the genotypes for all the characters studied, indicating availability of wide range of variability among the genotypes. Higher values of PCV and GCV were recorded for grain yield/plant, harvest index, tillers/plant and biological yield/plant. Heritability estimates were highest for 1000 grains weight followed by days to heading,grain yield/plant andplant height. Theestimates of genetic advance(GA) were highestfor grain yield/plant, harvest index and biological yield/plant. High heritability along with high genetic advance (per cent of mean) was observed for grain yield/plant, harvest index and biological yield/plant which suggested that selection for these characters would be more effective for desired genetic improvement.